2020
DOI: 10.1515/ijamh-2020-0111
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 on TikTok: harnessing an emerging social media platform to convey important public health messages

Abstract: ObjectivesTikTok is a popular social media platform, especially among those who are 13–24 years of age. The purpose of this cross-sectional study was to describe the content of COVID-19 material on TikTok.MethodsA total of 100 videos posted under the hashtag #Coronavirus were included in this study along with all (n=17) posts uploaded by the World Health Organization (WHO).ResultsOverall, these videos were viewed 1,194,081,700 times. The most commonly cited topics included anxiety (14.5%) with more than 190.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 4 publications
(3 reference statements)
5
95
0
5
Order By: Relevance
“…However, few previous studies have characterized whether the content of social media campaigns initiated by the health care community are truly unique. For example, TikTok videos about COVID-19 accumulated over 1 billion views; however, an analysis of these videos reports that only a small portion were led by health care professionals, and that few—even those developed by the World Health Organization—included actionable tools to prevent or handle the pandemic [ 23 , 24 ]. Another study reported that a Twitter campaign to raise skin cancer prevention awareness led to nearly 12 million impressions on social media [ 25 ] but did not examine content or tone of shared posts.…”
Section: Discussionmentioning
confidence: 99%
“…However, few previous studies have characterized whether the content of social media campaigns initiated by the health care community are truly unique. For example, TikTok videos about COVID-19 accumulated over 1 billion views; however, an analysis of these videos reports that only a small portion were led by health care professionals, and that few—even those developed by the World Health Organization—included actionable tools to prevent or handle the pandemic [ 23 , 24 ]. Another study reported that a Twitter campaign to raise skin cancer prevention awareness led to nearly 12 million impressions on social media [ 25 ] but did not examine content or tone of shared posts.…”
Section: Discussionmentioning
confidence: 99%
“…They are being used to monitor the progression of COVID-19 pandemic, to announce public policies and restrictions, to disseminate medical information or health advice, to deliver remote health care, and even to describe the geographic spread of COVID-19 which has been proven very effective. [26][27][28][29][30][31] In Klaten, the government used its official website and Instagram to deliver health messages, policies and monitor progressions. 21 We suggest that they should design an appealing public health poster to encourage people with chronic diseases, specifically hypertension, to see their physicians with masks, face shield and appropriate hand hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Since its creation, the popularity of TikTok has increased rapidly, with more than 800 million active users in 2020 [ 15 ]. During the COVID-19 pandemic, TikTok became an indispensable source of information and communication channel for the general public and between government organizations and citizens [ 16 ]. Second, extant studies have predominantly explored possible influencing factors through the lens of media type, government type, content type, media richness, message style, and interactive features, with limited effort paid to specific influencing mechanisms [ 1 , 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%